Stability Analysis and Development of a New Derived Scheme for the Solution of Riccati Equation - Fadugba, S.E.; Adeniji, A. A.; Mugisha, S. B. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper proposes a new scheme for the solution of first order Riccati ordinary differential equations by means of the transcendental function of exponential type. The properties of the scheme were analyzed and investigated. Four numerical examples have been solved to test the performance of the scheme against exact solution and in terms of the absolute relative errors with different step sizes. The comparative analyses of the results were also presented.